Pengaruh Penggunaan Aplikasi E-Book Senam Hamil terhadap Penurunan Nyeri Punggung Bawah pada Ibu Hamil Trimester II dan III: The Effect of Using a Pregnancy Exercise E-Book Application on Reducing Lower Back Pain in Pregnancy Women in the Second and Third Trimesters - Mediastuti, Elsa Puji; Septiani, Eichi (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Pregnancy is a time when mothers experience physical and psychological changes. These physical changes can sometimes cause discomfort, including lower back pain. Other predisposing factors for back pain include weight gain, changes in posture due to uterine enlargement, previous back pain, and repetitive stretching. The purpose of this study was to analyze the effect of a pregnancy exercise e-book application on reducing lower back pain in pregnant women in their second and third trimesters. The quantitative research method used a pre-experimental design with a one-group pretest-posttest design. The study was conducted at the independent practice of Midwife N in Karawang Regency in May 2025. Total sampling was used for sampling, with 35 pregnant women as respondents. The research instrument was observation. Data processing involved editing, coding, scoring, and tabulation with Spearman Rank analysis. The results of the study showed that before using the pregnancy exercise e-book application, the majority of respondents experienced lower back pain with a scale of 4 (very painful) as many as 19 respondents (54.3%). While after using the pregnancy exercise e-book application, the majority of respondents experienced lower back pain with a scale of 3 (more painful) as many as 22 respondents (62.9%). The results of the Spearman Rank statistical test showed a p-value = 0.000 < α (0.05). This means that there is an effect of using the pregnancy exercise e-book application on reducing lower back pain in pregnant women in the second and third trimesters. In conclusion, pregnant women in the second and third trimesters are expected to be more active in using the pregnancy exercise e-book application so they can learn interesting features in implementing pregnancy exercises.